STAGE DIRECTIONS AND DRAMATIC COMMUNICATION (Heritage, 2020)
According to various theoretical perspectives, views of didaskalia as a literary and theatre term have been changing from paratext through element in secondary text (Pfister) to essence of drama. Therefore, meaning of stage directions can be important for an overview of communication strategies in drama, such as multimedia, issue of auctorial voice in drama, and complex relationship between dramatic text and staging. Also, as an element in a secondary text, stage directions can maintain certain degree of independence, which emphasizes their distinct nature. This paper shows how various meanings of stage directions can fundamentally change the way we approach drama.
Keywords: didaskalia, stage directions, theatre play, auctorial voice, epic treatment of drama